2022
DOI: 10.1007/s11523-022-00892-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment with Nivolumab or Cabozantinib for Metastatic Renal Cell Carcinoma (mRCC) in the Veneto Region of Italy: Results of AMOUR Study

Abstract: Background Second-or third-line treatment options for metastatic renal cell carcinoma (mRCC) have dramatically changed in the last few years. There are no criteria for the choice between nivolumab and cabozantinib, which both demonstrated overall survival (OS) gain in pivotal trials. Objective We conducted an analysis of oncological outcomes in patients treated in the Veneto Region (Italy), studying different sequences of TKI-nivolumab-cabozantinib or TKI-cabozantinib-nivolumab in a publicly funded healthcare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…Cabozantinib was frequently used as second-line treatment, mostly after front-line sunitinib or pazopanib therapy, or as a third-line treatment, often after nivolumab. This finding is in line with another Italian analysis ( 17 ). When, however, cabozantinib was given as third-line treatment or beyond, a large number of different sequencies were reported and no pattern of therapies use could clearly be identified.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Cabozantinib was frequently used as second-line treatment, mostly after front-line sunitinib or pazopanib therapy, or as a third-line treatment, often after nivolumab. This finding is in line with another Italian analysis ( 17 ). When, however, cabozantinib was given as third-line treatment or beyond, a large number of different sequencies were reported and no pattern of therapies use could clearly be identified.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results emerged in the International Metastatic RCC Database Consortium, involving 413 patients from various countries, where the median times to cabozantinib treatment failure were 8.3 months for first-line, 7.3 months for second-line, 7.0 months for third-line and 8.0 months for fourth-line treatment ( 16 ). A recent, smaller study conducted in northeastern Italy reported a median duration of treatment of 6.6 months for second-line and 7.5 months for third-line cabozantinib use, thus confirming the activity of cabozantinib regardless of its line of use ( 17 ). Our finding of a median treatment persistence of cabozantinib of 8.7 months is, therefore, consistent with previous results from other unselected European and worldwide RCC patient populations.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Given the help of RWE research, the utility and application of cancer therapies can be studied, e.g., in second- or third-line treatment where several equivalent options exist. A recent real-world analysis showed that nivolumab rather than cabozantinib was administered as a second line to metastatic renal cell carcinoma (mRCC) patients, even though there were no criteria of favoring one or the other on the basis of former RCT results, and real-world cost-effectiveness of both treatments seemed to be similar [ 35 ]. In another RWE study in mRCC patients, those with a clear cell histology and good risk features had a significantly longer progression-free survival with cabozantinib—thus, certain subgroups of patients may benefit from cabozantinib rather than from nivolumab [ 36 ].…”
Section: Resultsmentioning
confidence: 99%